Microbial Styrene Degradation - Tischler, Dirk (SpringerBriefs in Microbiology, 2015)
This book describes the complex processes involved in styrene degradation by microbes, including highly adaptive microorganisms, the various enzymes involved in styrene biodegradation, new styrene-catabolic routes, novel regulatory mechanisms, and the genes coding for styrene metabolizing enzymes. Numerous biotechnological applications are discussed, such as the development of sustainable eco-friendly technologies as well as the use of styrene degrading microorganisms and their enzymes as a rich resource for biotechnology.